PENGARUH TAYANGAN MY TRIP MY ADVENTURE DI TRANS TV TERHADAP PENGETAHUAN WISATA SISWA - Tegar Prasetiyo Tegar; Tina Agustari (Jurnal Ilmiah Dinamika Sosial, 2021)
Television as a medium of mass communication has the function of informing, educating, and entertaining. One of the TV programs that have this function is My Trip My Adventure program. The purpose of this study was to see the impact of My Trip My Adventure on students' travel knowledge. Will students who have watched My Trip My Adventure get travel knowledge. The effect is revealed based on interest in My Trip My Adventure and expectations of the development of individual cognitive abilities on tourist information from this show. The research method used is quantitative with a positivism paradigm. The research was conducted by collecting primary data through surveys, then analyzed using descriptive analysis methods. The population of this study was students of SMKN 29 Jakarta, class 10 for the 2020-2021 academic year, totaling 338 students, with a minimum sample of 78 students. The results of this study indicate that My Trip My Adventure shows that Indonesian tourism tends to affect how individuals process information about Indonesia's tourism potential and Indonesian cultural diversity. In addition, the My Trip My Adventure program, which educates people to care about the environment, influences the audience's decision to participate in protecting nature. This study concludes that My Trip My Adventure on Trans Tv has a significant effect on students' travel knowledge. Key word: My Trip My Adventure shows, television media, student tourism knowledge.